2019
DOI: 10.11648/j.ajns.20190805.17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preventive Bundle Guidelines on Nurses’ Knowledge and Compliance Regarding Pressure Ulcer Among Critically Ill Children at Pediatric Intensive Care Unit

Abstract: Pressure ulcers are a common and highly relevant professional care issues in pediatric intensive care units. The aim of this study was to evaluate the effect of preventive bundle guidelines on nurses' knowledge and compliance regarding pressure ulcer among critically ill children at Pediatric intensive care unit. Research design: A quasi-experimental design was used. Settings: This study was conducted at the pediatric intensive care unit in Benha Specialized Pediatric Hospital. Sample: A Convenient sample of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…(30) The present study showed improvement in the total scores of the studied nurses' knowledge immediately and three months after attending the educational program in comparison to their knowledge before the educational sessions this improvement in nurses' knowledge was similar to Mohamed et al (2019) who conducted a study at Banha pediatric hospital to assess the effect of guidelines regarding pressure ulcer preventive measures and reported a remarkable improvement in nurses' knowledge after the implemented program in their study. ( 31) Regarding the total scores of nurses' practices about acquired skin injuries in the previously mentioned neonatal intensive care settings, nurses displayed significant progress concerning the overall neonatal skin care and prevention of acquired skin injuries. These results are concurrent with the intended outcome of the educational program which aimed to enhance nurses' performance regarding neonatal skin care.…”
Section: Results: Figures (1)mentioning
confidence: 99%
“…(30) The present study showed improvement in the total scores of the studied nurses' knowledge immediately and three months after attending the educational program in comparison to their knowledge before the educational sessions this improvement in nurses' knowledge was similar to Mohamed et al (2019) who conducted a study at Banha pediatric hospital to assess the effect of guidelines regarding pressure ulcer preventive measures and reported a remarkable improvement in nurses' knowledge after the implemented program in their study. ( 31) Regarding the total scores of nurses' practices about acquired skin injuries in the previously mentioned neonatal intensive care settings, nurses displayed significant progress concerning the overall neonatal skin care and prevention of acquired skin injuries. These results are concurrent with the intended outcome of the educational program which aimed to enhance nurses' performance regarding neonatal skin care.…”
Section: Results: Figures (1)mentioning
confidence: 99%